Pemanfaatan Bioretensi Buatan Sebagai Upaya Pengelolaan Air Hujan Untuk Peningkatan Kualitas Air - Endah Lestari (Sekolah Tinggi Teknik - PLN, 2021)
Water treatment priority water resources that are approved for air retention, Increased peak flow and improved water quality with regard to nutrients, pollutants, heavy metals and sediments. Bioretensi system is one alternative in improving air quality from rainwater runoff and reducing peak loads which also reduces runoff volume due to rain water.Management of urban water resources must be adapted to local conditions and sustainable. Bioretensi is a local infiltration media consisting of mixed soil and vegetation to absorb and manage rainwater so that it does not direct to the air body. The study was approved by the experimental research carried out with further research namely Bucket Bioretensi Design, installation, and testing. Some of the tests conducted on Bucket Bioretensi are rainwater quality testing, studying the level of infiltration by comparing the volume of inflows when opening a biretensi box and the volume of exits after going through a Bucket Bioretency. Bioretensi Bucket is made from used jerry cans with a capacity of 20 liters with dimensions of 27cm x 23cm x 37cm. Material obtained from high density polyethylene HDPE. After experimenting with Bucket Bioretensi I produced 25% of the volume of air coming out, so 75% of the air received into the Bucket Bioretency system. Water coming out of the Bucket Bioretensi will visit the laboratory to test the air quality.